MELIHAT POTRET HARMONISASI HUBUNGAN ANTARUMAT BERAGAMA DI INDONESIA - Izzah, Lathifatul (UIN Sunan Kalijaga Yogyakarta, 2013)
Harmony and conflict can be said to have derived from plurality. Yet plurality may beget harmony if people have embraced the inclusive or pluralist attitude. Conversely, plurality may also generate conflict if people chose to be exclusive, apathetic, as well as refuse to manage plurality. In the light of this reality, this article seeks to explore questions such as what are the forms of inter-religious relations in this country and are the for ms in line with the sociohistorical and cultural background of Indonesian society. Is the current shape of relationship between religious communities an ideal or suitable one?From the aforementioned questions it can be noted that the relationship between religious communities that develop and thrive in Indonesia take the shape of tolerance, interfaith harmony, interfaith dialogue, interreligious dialogue and cooperation. Indonesia is an archipelagic country which has a large and diverse area, especially in terms of demography, topography and geography. Indeed the types of relation between individuals and religious adherents in each region are different. A suitable pattern of harmonic relation in one place may not work quite well in another. In rural or coastal areas as well as in agricultural societies the values of tolerance and dialogue themselves may be supportive in preventing conflict. Whereas in urban areas or industrial cities it is most likely that tolerance alone is not enough, if it was not balanced with dialogue and cooperation among individuals and groups. Hence the values of dialogue and cooperation between individuals and groups must be developed in any ideal society, especially in the attempt to build har monic relationships among interadherents of religion or between religious communities with government.